A influência do associativismo no espaço urbano em dois municípios da região metropolitana de Maringá - os casos de Sarandi e Paiçandu-PR - Silva, Juliano Alves (2008)
In this dissertation reflect itself about the process of constitution of an association of the perspective of an intra-urban dynamics, involving Maringá, Sarandi and Paiçandu, marked by conditions of segregation social and spatial of the population of the last two. The two municipal districts are part of the urban agglomerate of the Maringá Metropolitan Area, but the lived realities are quite different. From the birth, the urban space of Maringá was drifted and endowed with minimum urban infrastructure in their neighborhoods. Sarandi and Paiçandu appeared while municipal districts and they grew in a disordered way and without investments in urban equipments. Along the years, the hard-working population of Maringá looked for home in those outlying cities, since the costs were smaller. That dynamics did with that it increased the population size of Sarandi and Paiçandu quickly, in a context of countless deficiencies of the urban structure. The organization of the population in residents associations comes as a road in the search of the improvement of the life quality. The field work developed, based on interviews with the presidents of the community associations of neighborhoods of Sarandi and Paiçandu, made possible to conclude that several organization apprenticeships exist. It was possible to notice that Sarandi and Paiçandu live different moments in this type of association fight, the first is has in one moment in that it tries to consolidate the relationships with the power publish and second, still tries to attract a larger number of people to participate in the meetings that became the process more dynamical